Modelling the effect of buyer power on the margins of commodity plastics - Cowley, P. R. (Cranfield School of Management, 1983)
In the last decade, large sectors of the chemical and plastics industries in the USA and West Europe have suffered drastic declines in price and gross margin during periods of low utilisation of industry capacity.This paper shows that the major changes in gross margin observed for some commodity plastics can be modelled successfully in terms of the balance between buyer power and seller power. These industries have visibility of prices and industry occupacity and comparable concentrations of sellers and important buyers. The modelling follows Burgess(this journal 1981) in expressing buyer and seler power as simple functions of buyer and seller concentrations, industry occpacity and 'cohesion' between sellers. This work provides a first practical test of this new approach. It is shown that the model fits the observed data best if the 'cohesion' declines as occupacity declines. The explanatory power using only three variables is extra-ordinarily good. It is suggested that the approach would be useful in understanding the behaviour of other 'near-commodity', capital-intensive businesses, and in helping to distinguish between those businesses where margins are likely to remain relatively stable and those which might face drastically declining magins if the industry occupacity declines or new entrants change the balance between sellers and buyers.